Kerala: Health Tourism Hub for Ayurveda - Padmasani, Dr; Remya, V. (International Journal of Social Sciences and Management, 2015)
Health/Medical tourism is a booming niche tourism market in the tourism industry. The main reason for the increasing trend is the high cost of treatment, long waiting time, less insurance coverage in developed countries and the attitude of people to spend holidays in a quality manner with the aim of improving health. In India, Kerala is emerging as a prime health tourism hub for its Ayurveda packages. The state attracts millions of foreign and domestic tourists to visit the state’s incredible heritage and experience the traditional nature based treatment therapies. The volume of tourist arrivals in Kerala had experienced a stupendous growth of 7.7 per cent in 2014 from 4.3 per cent in 2001 (Annual report of Tourism Statistics, Department of Tourism, Government of Kerala). This study aims to profile the tourists visiting Kerala for Ayurvedic treatment and to identify the destination image factors making Kerala an attractive place for Ayurveda health tourism. For this purpose, 150 domestic tourists availing Ayurvedic treatment in Kerala were selected on the convenience of the researcher. In order to analyse the objectives, the Descriptive Statistics, Factor Analysis and One-way ANOVA were employed and the results revealed that service quality, attraction, opportunity, benefits and promotion were the destination image factors making Kerala an attractive place for Ayurvedic Health Tourism. The present study identifies the strength of Kerala for Ayurveda health tourism which helps the destination managers and the service providers witha better understanding of the market for elevating Kerala and its Ayurveda in this niche market. Int. J. Soc. Sci. Manage. Vol-2, issue-3: 222-227 DOI: http://dx.doi.org/10.3126/ijssm.v2i3.12755